A neutralizing epitope on the SD1 domain of SARS-CoV-2 spike targeted following infection and vaccination - Seow, Jeffrey; Khan, Hataf; Rosa, Annachiara; Calvaresi, Valeria; Graham, Carl; Pickering, Suzanne; Pye, Valerie E.; Cronin, Nora B.; Huettner, Isabella; Malim, Michael H.; Politis, Argyris; Cherepanov, Peter; et al. (Cell reports (Cambridge), 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike is the target for neutralizing antibodies elicited following both infection and vaccination. While extensive research has shown that the receptor binding domain (RBD) and, to a lesser extent, the N-terminal domain (NTD) are the predominant targets for neutralizing antibodies, identification of neutralizing epitopes beyond these regions is important for informing vaccine development and understanding antibody-mediated immune escape. Here, we identify a class of broadly neutralizing antibodies that bind an epitope on the spike subdomain 1 (SD1) and that have arisen from infection or vaccination. Using cryo-electron microscopy (cryo-EM) and hydrogen-deuterium exchange coupled to mass spectrometry (HDX-MS), we show that SD1-specific antibody P008_60 binds an epitope that is not accessible within the canonical prefusion states of the SARS-CoV-2 spike, suggesting a transient conformation of the viral glycoprotein that is vulnerable to neutralization. [Display omitted] •A neutralizing epitope on spike subdomain 1 (SD1) is identified•The SD1 epitope is conserved between current SARS-CoV-2 variants and SARS-CoV•SD1 antibodies arise from infection and vaccination•Cryo-EM reveals the SD1 epitope is occluded on many SARS-CoV-2 spike structures Seow et al. identify a class of broadly neutralizing antibodies that bind a conserved epitope on the spike subdomain 1 (SD1) and that are elicited following infection and vaccination. The SD1 epitope is occluded on spike prefusion structures, suggesting binding to a conformational state of spike.